A retrospective study on the cardiac assessment of isolated sternal fracture patients based on radiographic and clinical outcomes. (September 2021) - Ahmadinejad, Mojtaba; Pak, Haleh; Soltanian, Ali; Pouryaghobi, Seyyed Mohsen; Mohammadzadeh, Sanaz; Ahmadi, Abtin; Ahmadinejad, Izadmehr
Abstract: Objective: Sternal fracture may be associated with major and serious injuries. In this study, the complications associated with isolated sternal fracture in trauma patients are evaluated based on radiographic and cardiac findings. Methods: This retrospective study was performed on patients with isolated sternal fractures admitted to the emergency department of (XXX) Madani Educational-Medical. Data regarding demographic information, mechanism of trauma, length of hospitalization, electrocardiography (ECG), cardiac enzyme, and chest radiography were recorded in the questionnaire for each patient. Results: The mean age of patients 41.2 + 11.04 years and 63.9% were male. The most common cause of the trauma was car accidents in 41% (25 cases). The mean duration of hospitalization was 1.54 ± 0.90 days. The mechanism of trauma was not associated with x-ray and computed tomography findings, p = 0.53 and p = 0.86, respectively. ECG findings were significantly related to x-ray and computed tomography outcomes, p < 0.001, respectively. Conclusion: Patients with isolated sternal fracture with displacement >0.5 cm and hematoma are likely to require cardiac consultation. Highlights: Sternal fracture may be associated with major and serious injuries. Approximately, 10% of all trauma cases are blunt trauma. Patients with isolated sternal fracture and hematoma are likely require cardiac consultation. The type mechanism of trauma may not predict radiographic findings.